Potential of Nanotechnology Treatment for Genetic Disorders - Fanesa Oktavianes Aulia; Siti Khofifah Dwi Febrianti; Ainun Rahmatun Nisak (Yayasan Adra Karima Hubbi, 2024)
Genetic disorders are complex health problems and are often difficult to treat conventionally. However, developments in the field of nanotechnology have opened up new opportunities for handling genetic diseases. Nanotechnology, or the creation of systems/devices at the molecular level, is a multidisciplinary scientific field that is experiencing rapid development. Nanotechnology offers innovative approaches to treating genetic disorders using the scale of nano-technology for drug delivery, gene therapy, and diagnostic molecular diagnostics to treat genetic disorders. Leveraging unique characteristics of a nanomachite, such as its size, shape, and functionality, can open a new path for more effective treatment and personalization for individuals suffering from genetic disorders. While still in the development stage, these developments promise a revolution in treatment of future genetic diseases